“Shared learning” for building urban climate resilience – experiences from Asian cities - Orleans Reed, Sarah; Friend, Richard; Toan, Vu Canh; Thinphanga, Pakamas; Sutarto, Ratri; Singh, Dilip (Environment and Urbanization, 2013)
This paper considers how resilience thinking and, in particular, its e mphasis on learning has been applied in 10 cities in Vietnam, India, T hailand and Indonesia. Applying a “shared learning” approach in the As ian Cities Climate Change Resilience Network (ACCCRN) has helped to cr eate or strengthen networks, build appreciation for complexity and unc ertainty among stakeholders, provide a space for deliberating concepts such as vulnerability and resilience, and build knowledge and capacit ies for stakeholders to engage and represent their own interests. Shar ed learning approaches face considerable challenges navigating politic ized urban environments, in which the nature and value of existing sys tems - and therefore the value of building resilience - are contested. This article suggests that deliberate, strategic intervention by faci litators may contribute to more transformative change on behalf of equ itable, socially just outcomes – and thus cautions against seeing urba n climate vulnerability as a technical challenge, or shared learning a s a “toolkit” for building resilience.